A strontium optical lattice clock with 1 × 10−17 uncertainty and measurement of its absolute frequency. (28th October 2020) - Hobson, Richard; Bowden, William; Vianello, Alvise; Silva, Alissa; Baynham, Charles F A; Margolis, Helen S; Baird, Patrick E G; Gill, Patrick; Hill, Ian R
Abstract: We present a measurement of the absolute frequency of the 5 s 2 1 S0 to 5s5p 3 P0 transition in 87 Sr which is a secondary representation of the SI second. We describe the optical lattice clock apparatus used for the measurement, and we focus in detail on how its systematic frequency shifts are evaluated with a total fractional uncertainty of 1 × 10 −17 . Traceability to the International System of Units is provided via comparison to International Atomic Time (TAI). Gathering data over 5- and 15-day periods, with the lattice clock operating on average 74% of the time, we measure the frequency of the transition to be 429 228 004 229 873.1 (5) Hz, which corresponds to a fractional uncertainty of 1 × 10 −15 . We describe in detail how this uncertainty arises from the intermediate steps linking the optical frequency standard, through our local time scale UTC(NPL), to an ensemble of primary and secondary frequency standards which steer TAI. The calculated absolute frequency of the transition is in good agreement with recent measurements carried out in other laboratories around the world.